HIV-1 drug resistant mutations in chronically infected teatment naïve individuals in the pre-ARV era in Nigeria. (2012)
In Nigeria the Federal Government rolled out antiretroviral drugs for the management of HIV infection in year 2002. This study was carried out to determine the circulating antiviral drug mutations among ARV naïve patients with chronic HIV infection during the pre-ARV roll out era in the country. DNA was extracted from stored whole blood samples collected from 75 HIV positive patients attending the Medical outpatient clinic between December 1996 and November 2001. The Reverse transcriptase (RT) and the protease (PR) regions of the viral genome were amplified by nested PCR and then sequenced by cycle sequencing and analyzed using the ABI 3100 DNA sequencer to determine the mutations associated with protease inhibitors (PI), nucleoside reverse transcriptase inhibitors (NRTI) and non-nucleoside reverse transcriptase inhibitor (NNRTI). Ten of the 64 (15.6%) samples with positive PCR had mutations for PR inhibitors (PI) including R8D, I 15V, G16E, M36I, M46L, L63P and H69K, while 5 of 63 harbored RT inhibitor (NRTI/NNRTI); V179I, A98T, V179E and A98S. Detection ofARV drug resistant mutations when ARV was not known to be in use in Nigeria calls for caution in the interpretation of drug resistance profile of HIV-1 from infected persons on treatment ARVs in the country.